“Millennial Generation Strategies in Facing Opportunities and Challenges of Entrepreneurship in the Digital Era 4.0” at the Da’arul Hijrah Islamic Boarding School - Chandra Zaky Maulana; Lemiyana; Deky Anwar; Nur Syamsiyah; Nadya Jovita (CV. Doki Course and Training, 2023)
The increasing number of internet users for commerce has led to the emergence of new businesses that are now widely referred to as start-up businesses. All of these businesses are engaged in trade and services that fulfill daily needs, the majority of which are online. This research aims to review some literature, data and facts about the start-up business phenomenon. Based on the development of start-up business knowledge, there are several things that must be done in digital start-up marketing activities to reach the target market and anticipate competition, namely the dissemination of information by using various digital media to spread or distribute related to the digital business being run. Utilizing opportunities in the digital world is still difficult for young people today, because they have not thought about becoming an entrepreneur. At the stage of the entrepreneurial formation process, they need support from their environment. Every minute a new digital start-up appears with almost the same features as one another, so the skills, innovation and creativity that young people tend to have can be applied.